ISTIHSAN: Interconnection Of Traditional And Contemporary Thought - Kholik, Abdul; Mustofa, Mustofa (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2023)
Istihsan, as one of the methods of legal interpretation in usul fiqh, has long been a focus of attention in the study of Islamic law. This research aims to compare the concept of istihsan across various sources of usul fiqh through the methodology of literature review. The results of this research is that the understanding of istihsan in different sources of usul fiqh exhibits variations but shares a common goal of applying legal flexibility in specific contexts. The research employs a literature review methodology to identify and analyze relevant literature on istihsan from various sources of usul fiqh. The initial step involves the identification of literature, including books, scholarly articles, and other reliable sources. Subsequently, a literature analysis is conducted to identify differing perspectives in understanding istihsan, including the approaches used by scholars from different schools of thought. This research provides deeper insights into how istihsan is applied in various contexts of usul fiqh, utilizing the literature review methodology. As a result, this study encourages a better understanding of the connection between traditional comprehension and the application of istihsan in responding to changes and complexities in modern society.